К ВОПРОСУ О ПОНЯТИИ «СИН» (性) В ТРАКТАТЕ «СЮНЬ-ЦЗЫ»: ТЕРМИНОЛОГИЧЕСКИЕ УТОЧНЕНИЯ - ГОРДИЕНКО, Андрей Витальевич (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2023)
The article attempts to outline the terminological role of the concept of xing (性) in Xunzi by reconstructing its terminological context. The author establishes that the concepts that make up this context, such as «simplicity» (pu 朴), «raw material» (cai 材), «ability / skill» (cai 才), «manifestations» (qing 情), «substance» (zhi 質), «realia» (shi 實), form a developed system, within which xing can be defined as something that endows living things by sensation’s unity.